(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research is to discover the quality of services provided by the Super specialityHospitals, Chennai and helps to know the satisfaction levels of the patients. A measure of service quality and patient satisfaction in various aspects of treatments and including the effectiveness of their care and their level of responsiveness and assurance. Satisfaction is predominant variable when delivering any kind of a service, but recently increase issues in the healthcare sector. Patient Satisfaction is one of the variables for measuring the quality in health care. This study provides is based on the survey questionnaire answers about Super speciality Hospitals with helpful guidelines to improve the quality of service and patients satisfaction in the Hospitals